Child Neurology: Aicardi-Goutières Syndrome Presenting as Recurrent Ischemic Stroke. (30th August 2022) - Kuang, Shen-yi; Li, Yao; Yang, Shi-Lin; Han, Xiang
Abstract : Aicardi-Goutières syndrome (AGS) is a rare, single-gene disorder, characterized by neurologic and skin involvement with an increased level of interferon-α (IFN-α) in the CSF. We describe the case of a young patient presenting with recurrent ischemic stroke. Evaluation revealed the presence of chilblains, white matter abnormalities, cerebral atrophy, and raised IFN-α in the CSF. Compound heterozygous variants of TREX1 were detected, confirming a diagnosis of AGS. After excluding other causes, we attributed the stroke to AGS. Tofacitinib, a Janus kinase inhibitor, was administered to our patient in addition to antiplatelet drugs. There was no recurrence of stroke during 3-month follow-up. This is a rare case of recurrent stroke in TREX1 -mutated AGS. Small vessel involvement has been previously demonstrated to play a significant role in the pathogenesis of AGS. This microvascular mechanism might explain the occurrence of ischemic stroke in our patient. For young patients with stroke and multiple system involvement, genetic disorders including AGS should be considered.